Subjective wellbeing in a sample of South African, Xhosa people with schizophrenia - Boshe, Judith (Department of Psychiatry and Mental Health, 2020)
Subjective well-being when on neuroleptic treatment (SWBN), has been established as a good predictor of adherence, early response and prognosis in patients with schizophrenia(1, 2). The 20-item subjective well-being under neuroleptic treatment scale (SWN-K 20) is a self-rating scale that has been validated to measure SWBN(3). However, the SWN-K20 has not been previously used in a Low- and Middle-income country (LMIC). Aims and Objectives: This study explored the psychometric properties of SWN-K20 in a sample of Xhosa speaking African patients with schizophrenia, and investigated factors associated with SWBN in this population. Methods: As a part of a large genetic study, 244 study participants with a confirmed diagnosis of schizophrenia completed the translated SWN-K 20 scale. Internal consistency analysis was performed, and convergent analysis and exploratory analysis were conducted using Principal Component Analysis (PCA).Varimax rotation method was selected as we did not assume any correlation of the factors(4). Linear regression methods were used to determine predictors of SWBN in the sample population. Results: The PCA extracted 4 components which cumulatively explained 52.21% of the total variance. The internal consistency of the SWN-K 20 was 0.86 and those of the sub-scales ranged between 0.47 and 0.59. The total scores of the SWN-K 20 demonstrated moderate correlation r= 0.44 with GAF scores. The sub-scale scores had lower correlations ranging between r=.41 and r=.30 with the GAF scores. The total scores on SWN-K20 scale were used to explore factors influencing SWBN. There was a significant correlation between overall subjective well-being score with higher education level, increased illness severity and GAF scores. Discussion and Conclusion: The isiXhosa version of the SWN-20 scale can be used for clinical and research purposes in LMICs but predictors of SWBN in this population differed from those previously established in (high income countries) HICs. The individual sub-scales of the SWN-K20 were less reliable when translated into isiXhosa and hence the subs-scales were not a meaningful measure of specific domains of wellbeing . These findings merit evaluation to determine whether cultural and linguistic specific sub-cales might provide further insight and recommendations for use in South African context. Predictors of SWBN in this LMICs population were not comparable to those in HICs setting(5, 6). Older patients with lower baseline level of education, poor global functioning and less severe symptoms were noted to have lower SWBN and hence at risk of poor compliance. This information could provide guidance for clinicians, researchers and interventions that aim at improving compliance and the treatment experiences of this patient group.